Pengaruh Media Berbasis Permainan Edukatif Wordwall Terhadap Kemampuan Berpikir Kritis Mata Pelajaran IPAS - Rahayu, Putri; Hidayat, Taufik; Makmun; Mustamiroh (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2025)
The low critical thinking skills of fifth-grade students at a private elementary school in Samarinda, especially in the IPAS (Social Studies and Science) subject, led to this research to examine the effect of the word wall-based educational game media on the student’s critical thinking skills. This study uses a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The sampling technique used in this study is saturated sampling, where the entire population of fifth-grade students is selected as the research sample. Data in this study were collected through questionnaires, tests, and documentation. Data analysis techniques included normality tests, homogeneity tests, independent sample t-tests, and n-gain score tests. The result shows that the significance value in the independent sample t-test is 0.002 0.005, indicating a significant effect of word wall-based educational game media on students’ critical thinking skills in the IPAS subject. Furthermore, the word wall media is effective in improving students’ critical thinking skills, with an experimental class n-gain score of 0.48 (moderate category) and a control class n-gain score of 0.27 (low category). The findings of this study suggest that the use of Wordwall media can enhance student motivation and engagement in the learning process, which can subsequently contribute to the improvement of their critical thinking skills. Based on these findings, the researcher recommends that future studies explore other learning materials or topics as a focus for research so that the findings can be more varied.